2011
DOI: 10.1016/j.ajpath.2011.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Wild-Type or a Centronuclear Myopathy Mutant of Dynamin 2 in Skeletal Muscle of Adult Mice Leads to Structural Defects and Muscle Weakness

Abstract: Dynamin 2 (DNM2) is a large GTPase implicated in many cellular functions, including cytoskeleton regulation and endocytosis. Although ubiquitously expressed, DNM2 was found mutated in two genetic disorders affecting different tissues: autosomal dominant centronuclear myopathy (ADCNM; skeletal muscle) and peripheral Charcot-Marie-Tooth neuropathy (peripheral nerve). To gain insight into the function of DNM2 in skeletal muscle and the pathological mechanisms leading to ADCNM, we introduced wild-type DNM2 (WT-DNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(130 citation statements)
references
References 41 publications
8
120
0
2
Order By: Relevance
“…Moreover, biochemical analysis suggests several DNM2 CNM mutants increase DNM2 GTPase activity and oligomerization (26,27). Furthermore, overexpression of WT DNM2 by AAV or by miR-133a inhibition resulting in increased DNM2 expression promoted muscle defects and centralization of nuclei in mouse muscle (28,30). We thus hypothesized DNM2-CNM mutations are gain-of-function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, biochemical analysis suggests several DNM2 CNM mutants increase DNM2 GTPase activity and oligomerization (26,27). Furthermore, overexpression of WT DNM2 by AAV or by miR-133a inhibition resulting in increased DNM2 expression promoted muscle defects and centralization of nuclei in mouse muscle (28,30). We thus hypothesized DNM2-CNM mutations are gain-of-function.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported in vivo by either knockin or overexpression of the most common CNM-DNM2 patient mutation in mice, which induced CNM-like features at adulthood (28,29), indicating that the disease is not due to haploinsufficiency. Overexpression of WT DNM2 also caused similar CNM-like perturbation to the muscle, albeit to a lesser extent (28,30).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…18 In addition, the perinatal syndrome described in our patients, our in situ Dnm2 hybridization observations and knockdown experiments in zebrafish are consistent with Dnm2 having a role during embryonic development. Although features of the CNM pathology can be reproduced both by knock-in and Adeno-associated virus-mediated exogenous expression approaches for the most prevalent ADCNM-causing DNM2 mutation (R465W), 19,20 Durieux et al 20 reported that the homozygous knock-in mice died shortly after birth. These observations highlight the difference in the severity of the pathology at the heterozygous and homozygous state and are consistent with the differences in the phenotypic spectrum observed for the p.Phe379Val heterozygous and homozygous carriers.…”
Section: Discussionmentioning
confidence: 99%